Α-Tocopherol-based cationic amphiphiles with a novel pH sensitive hybrid linker for gene delivery. Issue 16 (6th April 2018) - Muripiti, Venkanna; Rachamalla, Hari Krishnareddy; Banerjee, Rajkumar; Patri, Srilakshmi. V.
Abstract : Endosomal escape is one of the barriers for the efficient liposomal gene delivery. Abstract : Endosomal escape is one of the barriers for the efficient liposomal gene delivery. To address this and based on earlier encouraging results using tocopherol cationic lipids, we elaborated chemical modifications on tocopherol cationic lipids by introducing a novel hybrid pH sensitive linker "ether-β-hydroxy-triazole" between tocopherol, the anchoring moiety and the basic tris(2-hydroxy ethyl)quaternary ammonium head group (Lp2 ). As control lipids we designed two lipids (Lp1 andLp3 ), one is with only the ether-β-hydroxy linker in between α-tocopherol and quaternary tris(2-hydroxyethyl)ammonium (Lp1 ) and the other is with the same novel hybrid linker i.e. "ether-β-hydroxy-triazole" between the α-tocopherol linked and quaternary tris-ethyl ammonium head group (Lp3 ). Liposomes were formulated with a combination of a well-known co-lipid, 1, 2-dioleoyl- sn-glycero -3-phosphoethanolamine (DOPE) and biophysical characteristics such as DNA binding, hydrodynamic diameters and global surface charges for liposomes and lipoplexes of respective lipids were evaluated. Cell viability assay and in vitro transfection studies were carried out in NIH3 T3, B16F10, HEK-293, and HepG2 cell lines. In vitro transfection data for the liposomes of lipids (Lp1, Lp2 andLp3 ) revealed that theLp2 lipid with a novel hybrid pH sensitive linker showed superior transfection efficiency when compared with the remaining two analogues. More importantly, Lp2 has shown a similar pattern of transfection efficiency in HepG2 and HEK-293 cell lines when compared with commercially available Lipofectamine 3000.